التعايش السلمي في ضوء مقاصد الشريعة الإسلامية:”سريلانكا” أنموذجا = Peaceful co-existence in the light of objectives of Sharia’h - Abdul Manas, Shayuthy; Mohamed Siddeek, Mohamed Ibrahim (Universiti Sultan Azlan Shah, 2016)
The study focuses on clarifying the concept of peaceful coexistence, and its principles in the perspective of the “Maqasid Al-Shariah, (objectives of Islamic “Shariah”) because, the most important purposes of “Maqasid AlShariah” are protection of soul, family, dignity and money. And also the establishment ofsecurity and peaceful life through the peaceful coexistence by following the basic foundations which are considered as important pillars of peaceful co-existence, these are nature, justice, freedom, and equality under the multiplicity of religions, different races and colors. Therefore, according to the interdependence between the objectives of “Shariah” and co-existence which is considered an important pillar of the social system, and the development of communities,the study focuses on highlighting some of the important problems that hinder the achievement of peaceful coexistence between Muslims and non-Muslims in the “Sri Lanka” due to the lack of knowledge about the reality of “Maqasid Al-Shariah” and its relationship to peaceful co-existence.